Legislative malapportionment and institutional persistence - Bruhn, Miriam (The World Bank, 2010)
This paper argues that legislative malapportionment, denoting a discrepancy between the share of legislative seats and the share of population held by electoral districts, serves as a tool for pre-democratic elites to preserve their political power and economic interests after a transition to democracy. The authors claim that legislative malapportionment enhances the pre-democratic elite's political influence by over-representing areas that are more likely to vote for parties aligned with the elite. This biased political representation survives in equilibrium as long as it helps democratic consolidation. Using data from Latin America, the authors document empirically that malapportionment increases the probability of transitioning to a democracy. Moreover, the data show that over-represented electoral districts are more likely to vote for parties close to pre-democracy ruling groups. The analysis also finds that overrepresented areas have lower levels of political competition and receive more transfers per capita from the central government, both of which favor the persistence of power of pre-democracy elites